Spherical silica powder
By controlling the number of water molecules and surface treatment, the dielectric loss tangent of spherical silica powder is optimized, and the problem of high dielectric loss tangent in the prior art is solved, and good compatibility with resin and dielectric characteristics optimization is achieved. Suitable for high-frequency equipment.
Patent Information
- Application Number
- CN202180030514.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-09-30
- Filing Date
- 2021-04-22
- Publication Date
- 2024-12-24
- Estimated Expiration
- 2041-04-22
AI Technical Summary
The existing spherical silica powder has a high dielectric loss tangent in the high frequency band, which is difficult to meet the low dielectric loss requirements of high-frequency equipment, and the existing surface treatment methods have no obvious effect on the millimeter wave band.
When the temperature is raised from 25°C to 1000°C at 30°C/min, the number of water molecules is controlled below 0.01 mmol/g, and the surface treatment is performed to reduce the dielectric loss tangent. The peak intensity ratio is determined by diffusion reflection FT-IR method. B/A is below 3.0, combined with high-temperature heating and vacuum firing, the polar functional groups are reduced and the specific surface area and average roundness of spherical silica powder are optimized.
It significantly reduces the dielectric loss tangent of the resin material, improves compatibility and adhesion with the resin, and is suitable for high-frequency band dielectric equipment, ensuring the optimization of dielectric characteristics.
Smart Images

Figure BDA0003904737530000141 
Figure BDA0003904737530000151 
Figure BDA0003904737530000171
Abstract
Description
Technical Field
[0001] The invention relates to spherical silicon dioxide powder with low dielectric loss tangent. Background Art
[0002] In recent years, with the increase in the amount of information communication in the communication field, the use of high frequency bands in electronic equipment and communication equipment is expanding. High frequency has the characteristics of wide bandwidth, linear propagation, and transmission, especially the frequency of 10 9 The use of frequency bands above GHz is becoming more common. For example, in the automotive field, millimeter-wave radars and half-millimeter-wave radars used for collision prevention use high frequencies of 76 to 79 GHz and 24 GHz, respectively, and are expected to become more common in the future.
[0003] With the application of high-frequency bands, the transmission loss of circuit signals has increased. Transmission loss generally includes conductor loss due to the skin effect of wiring and dielectric loss due to the characteristics of the dielectric material of the insulator constituting the substrate and other electrical and electronic components. Dielectric loss is proportional to the first power of the frequency, the half power of the dielectric constant of the insulator, and the first power of the dielectric loss tangent. Therefore, materials used in high-frequency band equipment are required to have low dielectric constants and dielectric loss tangents.
[0004] Polymer materials used in insulating materials generally have low dielectric constants but high dielectric loss tangents. On the other hand, ceramic materials often have opposite properties. In order to combine these two properties, polymer materials filled with ceramic fillers are being studied (e.g., Patent Document 1).
[0005] The dielectric properties of ceramic materials in the GHz band are known, for example, from non-patent literature 1, but they are all properties of sintered substrates. Silicon dioxide (SiO2) has a small dielectric constant (3.7) and a quality factor index Qf (the value obtained by multiplying the inverse of the dielectric loss tangent by the measured frequency) of about 120,000, and is expected to be a material for fillers with low dielectric constant and dielectric loss tangent. In addition, in order to facilitate the matching in the resin, the closer the filler shape is to a sphere, the more ideal it is, and spherical silicon dioxide (such as patent literature 2) can be easily synthesized, which has been used in many applications. Therefore, it is expected to be widely used in dielectric devices in high-frequency bands, etc.
[0006] However, there are a large number of adsorbed water and polar functional groups such as silanol groups on the surface of spherical silica particles, and there is a problem that the dielectric loss tangent ratio is particularly poor as a characteristic of the sintered substrate.
[0007] As a method for reducing adsorbed water and polar functional groups on the surface of filler particles, for example, non-patent document 2 studies a method of surface treatment using a silane coupling agent, but the dielectric loss tangent is hardly reduced at 1 to 10 MHz, and the effect in the millimeter wave band is not clearly described.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Publication No. 2014-24916
[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 58-138740
[0012] Non-patent literature
[0013] Non-patent document 1: International Materials Reviews vol. 60 No. 70 Supplementary data (2015).
[0014] Non-patent literature 2: IEEE Transactions on Dielectrics and Electrical Insulation Vol. 17, No. 6 (2010). Summary of the invention
[0015] The invention provides a spherical silicon dioxide powder with low dielectric loss tangent.
[0016] (1) A spherical silica powder characterized in that when the temperature is increased from 25°C to 1000°C at 30°C / min, the number of water molecules released at 500°C to 1000°C is less than 0.01 mmol / g, and the specific surface area is 1 to 30 m 2 / g.
[0017] (3) The spherical silica powder according to (1), characterized in that the wave number of the silica powder measured by diffuse reflectance FT-IR method is 3735 cm -1 ~3755cm -1 The peak intensity is set to A and the wave number is 3660 cm -1 ~3680cm -1 When the peak intensity of is defined as B, B / A is less than 3.0.
[0018] (3) The spherical silica powder according to (1) or (2), wherein the average roundness is 0.85 or more.
[0019] (4) The spherical silica powder according to any one of (1) to (3), which is surface-treated with a surface treatment agent.
[0020] (5) The spherical silica powder according to any one of (1) to (4), which is used by being blended with a resin.
[0021] (6) A resin composition comprising the spherical silica powder according to any one of (1) to (5) and a resin.
[0022] (7) The resin composition according to (6), wherein the resin is one or more selected from hydrocarbon elastomers, polyphenylene ethers, aromatic polyene resins, and bismaleimide resins.
[0023] (8) A cured product obtained by curing the resin composition described in (6) or (7).
[0024] According to the present invention, it is possible to provide spherical silica powder capable of reducing the dielectric loss tangent of a resin material such as a substrate. DETAILED DESCRIPTION
[0025] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to the following embodiments.
[0026] When the silica powder of the present invention is heated from 25°C to 1000°C at 30°C / min, the number of water molecules released at 500°C to 1000°C is 0.01 mmol / g or less. The amount of water released can be measured, for example, using a temperature degassing analyzer (TDS), where the temperature is raised from 25°C at 30°C / min, and the number of H2O released molecules is calculated from the area value in the range of 500°C to 1000°C of the mass spectrum (m / z=18) obtained by heating from 25°C at 30°C / min. The number of released molecules is preferably 0.008 mmol / g or less, and the lower limit is not particularly specified, but is actually 0.0001 mmol / g or more.
[0027] The silica powder of the present invention is preferably: the spherical silica powder before surface treatment is measured by diffuse reflectance FT-IR method at a wave number of 3735 cm -1 ~3755cm -1 The peak intensity is set to A and the wave number is 3660 cm -1 ~3680cm -1 When the peak intensity of is defined as B, B / A is less than 3.0. Usually, it is known that the wave number is 3735cm -1 ~3755cm -1 The peak is the isolated silanol group, with a wave number of 3660 cm -1 ~3680cm -1The peak is a hydrogen-bonded silanol group. In the present invention, focusing on the strength of the hydrogen-bonded silanol group, when B / A is 3.0 or less, the dielectric loss tangent of the resin composition can be sufficiently reduced. The lower limit is not particularly specified, but in fact it is above 0.01. It should be noted that it is difficult to correctly evaluate B / A because the isolated silanol group (A) disappears in the surface-treated silica. Therefore, it can be quantified using silica powder before surface treatment, or after the surface treatment agent is volatilized and decomposed by high-temperature heating, vacuum firing, cleaning with an organic solvent, etc. The number of H2O molecules that are separated at 500°C to 1000°C is important. In order to volatilize and decompose the surface treatment agent, it can be fired at a temperature below 500°C. The value of the silica powder before surface treatment is the same as the B / A when the treatment agent is removed after surface treatment. The presence or absence of a surface treatment agent can be evaluated, for example, by mass spectrometry or IR.
[0028] The specific surface area of the spherical silicon dioxide powder of the present invention is 1 to 30 m 2 / g. Specific surface area is greater than 30m 2 / g, it is difficult to incorporate into the resin, and less than 1m 2 / g, the dielectric loss tangent reduction treatment effect becomes smaller. The specific surface area is preferably 1 to 20 m 2 / g, more preferably 1 to 16 m 2 / g.
[0029] The average circularity of the spherical silica powder of the present invention is preferably 0.85 or more, more preferably 0.90 or more. If the average circularity is less than 0.85, when mixed with a resin, the viscosity may increase and the fluidity may decrease, and the processability and filling property may deteriorate.
[0030] The density of the spherical silica powder of the present invention is preferably 1.8 to 2.4 g / cm 3 If the density is less than 1.8, a large number of voids are contained in the particles, making mixing in the resin difficult. If the density is greater than 2.4, the crystal structure of silica contains α-quartz, cristobalite, etc., and there is a concern that the thermal expansion coefficient may increase, which may affect the physical properties.
[0031] The raw material silica powder of the present invention has an average roundness of 0.85 or more and a specific surface area of 1 to 30 m 2 / g of spherical silica powder can be used appropriately. The method for producing the spherical silica powder as a raw material includes, for example, a powder melting method in which the spherical silica powder is passed through a high temperature region of a temperature not lower than the melting point to form a spherical silica powder.
[0032] The spherical silica powder of the present invention can be manufactured by the following method: the raw silica powder is subjected to high temperature heating treatment while the powder is made to flow under an inert atmosphere or is heated in an electric furnace as a reduction reaction site. It can be manufactured by the following method: for temperature and time, when the temperature is raised from 25°C to 1000°C under the condition of 30°C / min, the number of water molecules separated at 500°C to 1000°C is 0.01mmol / g or less. Although it varies depending on the specific surface area of the raw silica powder, for example, it is treated in a rotary kiln at 700 to 1000°C under a nitrogen atmosphere or an argon atmosphere while making the powder flow for 1 to 24 hours, and then naturally cooled in the furnace. The electric furnace as a reduction reaction site is, for example, a carbon furnace whose furnace material is carbon. When the furnace material is other than carbon, it is fired in an atmosphere to which several % of hydrogen is added. After cooling to below 200°C, it is dried in a vacuum dryer and then recovered in a moisture-proof aluminum bag.
[0033] By using the above-mentioned manufacturing method, the adsorbed water and polar functional groups on the surface of the spherical silica particles can be reduced without changing the powder properties such as the specific surface area. Even after manufacturing, even if the particles are stored for one month under high humidity, such as 40°C to 90% RH, it can be expected that the amount of adsorbed water and polar functional groups on the surface of the particles will not change to the extent that the dielectric loss tangent of the spherical silica is increased.
[0034] The manufacturing method may include a step of classifying the powder to obtain a desired specific surface area and average particle size. As long as the heating temperature is below 1000°C, the specific surface area and average particle size will not change before and after heating, so it is preferred that the classification step is implemented before heating, and the heat treatment is performed after the desired specific surface area and average particle size are adjusted.
[0035] The obtained powder can be surface treated with a surface treatment agent to further reduce the surface polar groups and reduce the dielectric loss tangent. In addition, it is also expected to improve the fusion and adhesion with the resin interface. The surface treatment agent can be a treatment agent with good compatibility with the added resin type, or a treatment agent that is not easy to retain polar functional groups after surface treatment, for example, epoxy silanes such as γ-glycidoxypropyltriethoxysilane, β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, aminosilanes such as aminopropyltriethoxysilane, N-phenylaminopropyltrimethoxysilane, vinyl silanes such as vinyltrimethoxysilane, acrylic silanes such as acryloxytrimethoxysilane, silazanes such as hexamethyldisilazane, etc. The amount of treatment agent having a large number of polar functional groups such as aminosilane and acrylic silane is preferably as small as possible, for example, 1 part by mass or less relative to 100 parts by mass of spherical silica powder. After surface treatment, it is preferably recycled again in moisture-proof aluminum bags.
[0036] From the viewpoint of reducing the dielectric loss tangent, the impurities of alkali metals such as Na, Li, or K and metal elements such as Fe contained in the spherical silica powder of the present invention are preferably as small as possible. Other impurities are also preferably reduced as much as possible.
[0037] As a storage method for the spherical silica powder with reduced dielectric loss tangent of the present invention, it is preferred to use a moisture permeability of 0.1 (g / m 2 · Store in moisture-proof bags (24h or less), such as moisture-proof aluminum bags, PET / AL / PE laminated bags.
[0038] The spherical silica powder of the present invention is mixed with other powders having different specific surface areas, average particle sizes and compositions to obtain a mixed powder. By preparing the mixed powder, the dielectric constant, dielectric loss tangent, thermal expansion coefficient, thermal conductivity, filling rate, etc. when mixed with a resin can be more easily adjusted.
[0039] The spherical silica powder of the present invention and the mixed powder appropriately added are, for example, used in combination with a resin. That is, the present invention is preferably a resin composition comprising spherical silica powder and a resin. In addition, it is preferably a cured product obtained by curing the resin composition. As the resin used in the present invention, for example, polyethylene, polypropylene, epoxy resin, silicone resin, phenolic resin, melamine resin, urea resin, unsaturated polyester, fluororesin, polyimide, polyamide-imide, polyetherimide and other polyamides, polybutylene terephthalate, polyethylene terephthalate and other polyesters, polyphenylene sulfide, wholly aromatic polyester, polysulfone, liquid crystal polymer, polyether sulfone, polycarbonate, maleimide modified resin, ABS resin, AAS (acrylonitrile-acrylic rubber styrene) resin, AES (acrylonitrile ethylene propylene diene rubber styrene) resin, etc. can be cited.
[0040] The spherical silica powder of the present invention and the appropriately added mixed powder, especially in the case of substrate materials and insulating materials for high frequency, can be used in combination with known low dielectric resins used in this application. Specifically, it is combined with the following resins and crosslinked and cured as needed. As such a resin, for example, one or more selected from hydrocarbon elastomers, polyphenylene ethers, aromatic polyene resins, and bismaleimide resins can be used. Among them, hydrocarbon elastomers or polyphenylene ethers and bismaleimide resins are preferred. The mass ratio of the spherical silica powder and the mixed powder to these resins is arbitrary, but preferably in the range of 5:95 to 80:20, and more preferably in the range of 5:95 to 70:30.
[0041] <Hydrocarbon elastomer>
[0042] Among hydrocarbon elastomers, conjugated diene polymers are preferred. Among conjugated diene polymers, 1,2-polybutadiene is preferred. The number average molecular weight of hydrocarbon elastomers that can be appropriately used can be 1000 or more, preferably 10,000 or more. Examples of hydrocarbon elastomers include one or more elastomers selected from ethylene or propylene elastomers, conjugated diene polymers, aromatic vinyl compound-conjugated diene block copolymers or random copolymers, and their hydrogenates (hydrogenated products). As ethylene elastomers, ethylene-octene copolymers, ethylene-1-hexene copolymers and other ethylene-α-olefin copolymers, EPR, EPDM can be mentioned. As propylene elastomers, propylene-α-olefin copolymers such as atactic polypropylene, low-regular polypropylene, and propylene-1-butene copolymers can be mentioned.
[0043] <Conjugated diene polymer>
[0044] As conjugated diene polymers, polybutadiene and 1,2-polybutadiene can be cited. As aromatic vinyl compound-conjugated diene block copolymers or random copolymers and their hydrogenated products (hydrogenated products), SBS, SIS, SEBS, SEPS, SEEPS, SEEBS, etc. can be exemplified. 1,2-polybutadiene that can be suitably used is available as a product of JSR Corporation, for example, and liquid polybutadiene with product names of B-1000, 2000, and 3000 can also be obtained from Nippon Soda Co., Ltd. In addition, as a copolymer containing a 1,2-polybutadiene structure that can be suitably used, "Ricon 100" of Totalcry Valley Company can be exemplified.
[0045] <Polyphenylene ether>
[0046] As the polyphenylene ether, commercially available known polyphenylene ether can be used. The number average molecular weight of the polyphenylene ether is arbitrary. Considering the molding processability of the complex, the number average molecular weight is preferably 10,000 or less, and most preferably 5,000 or less. In addition, the number average molecular weight can preferably be 500 or more. In addition, when added for the purpose of curing the complex, it is preferred that the molecular end is modified, and / or it is preferred to have multiple functional groups in one molecule. As functional groups, allyl, vinyl, epoxy, etc. can be mentioned. As functional groups, free radical polymerizable functional groups are preferred. As free radical polymerizable functional groups, vinyl is preferred. As vinyl, (meth) acryloyl and aromatic vinyl are preferred. Furthermore, bifunctional polyphenylene ethers obtained by modifying the molecular chain with free radical polymerizable functional groups at both ends are particularly preferred. As such polyphenylene ethers, Noryl (trademark) SA9000 of SABIC and bifunctional polyphenylene ether oligomer (OPE-2St) manufactured by Mitsubishi Gas Chemical Co., Ltd. can be used.
[0047] <Aromatic polyene resin>
[0048] Aromatic polyene resins include divinylbenzene reactive multi-branched copolymers (PDV) manufactured by NIPPON STEEL Chemical & Material Co., Ltd. Such PDVs are described in, for example, the document "Synthesis of multifunctional aromatic vinyl copolymers and development of novel IPN-type low dielectric loss materials using the same" (Kawabe Masanori et al., Journal of the Electronic Packaging Society, p125, Vol. 12 No. 2 (2009)). In addition, aromatic polyene resins include aromatic polyene polymer resins having the above-mentioned aromatic polyene monomers as main constituent units.
[0049] <Bismaleimide resin>
[0050] The maleimides and bismaleimides that can be used in the present invention are described in International Publication No. 2016 / 114287 and Japanese Patent Application No. 2008-291227, for example, and can be purchased from Yamato Chemical Industry Co., Ltd. and Designermolecules Inc. From the viewpoints of solubility in organic solvents, high-frequency characteristics, high adhesion to conductors, and prepreg formability, these maleimide-containing compounds are preferably bismaleimides. From the viewpoints of solubility in organic solvents, high-frequency characteristics, high adhesion to conductors, and prepreg formability, these maleimide-containing compounds can be used as polyaminobismaleimide compounds. The polyaminobismaleimide compound is obtained, for example, by subjecting a compound having two maleimide groups at the end to a Michael addition reaction with an aromatic diamine compound having two primary amino groups in the molecule.
[0051] The spherical silica powder and mixed powder of the present invention can be used together with these resins to crosslink and cure using the following crosslinking materials and curing agents. As crosslinking materials, maleic anhydride, glycidyl (meth) acrylate, glycidyl (meth) acrylate, triallyl isocyanurate, tri(meth) acrylate isocyanurate, trimethylolpropane tri(meth) acrylate, etc. can be cited. In the case of trying to obtain high crosslinking efficiency with a small amount of addition, it is preferred to use a crosslinking material with a multifunctional group of more than two functional groups, and triallyl isocyanurate (TAIC) and trimethylolpropane tri(meth) acrylate can be exemplified. For the above-mentioned resins other than maleimide resins and bismaleimide resins, the above-mentioned maleimide resins and bismaleimide resins can be used as appropriate crosslinking materials. In addition, for the above-mentioned resins other than polyphenylene ether, the above-mentioned polyphenylene ether can be used as an appropriate crosslinking material. Relative to 100 parts by mass of the above-mentioned resin, the amount of the crosslinking material can be 0.1 to 30 parts by mass, preferably in the range of 0.1 to 10 parts by mass.
[0052] <Curing agent>
[0053] As the curing agent used, a known curing agent that can be used in the polymerization or curing of aromatic polyenes and aromatic vinyl compounds can be used. Such curing agents can be exemplified by free radical polymerization initiators, cationic polymerization initiators, and anionic polymerization initiators, but free radical polymerization initiators can be preferably used. Organic peroxide-based (peroxides), azo-based polymerization initiators, etc. are preferred, and can be freely selected according to the application and conditions. The catalogue of organic peroxides can be downloaded from the NOF homepage, for example, at the following website:
[0054] https: / / www.nof.co.jp / business / chemical / product01a.html
[0055] https: / / www.nof.co.jp / business / chemical / product01b.html
[0056] https: / / www.nof.co.jp / business / chemical / product01c.html.
[0057] In addition, organic peroxides are also recorded in the catalogs of Wako Pure Chemical Industries, Ltd. and Tokyo Chemical Industry Co., Ltd. The curing agent used in the present invention can be obtained from these companies. In addition, a known photopolymerization initiator using light, ultraviolet rays, or radiation can also be used as a curing agent. As a curing agent using a photopolymerization initiator, a photoradical polymerization initiator, a photocationic polymerization initiator, or a photoanionic polymerization initiator can be cited. Such a photopolymerization initiator can be obtained, for example, from Tokyo Chemical Industry Co., Ltd. Furthermore, it is also possible to cure by radiation or electron beams themselves. In addition, crosslinking and curing can also be performed by thermal polymerization of the raw materials contained without containing a curing agent. There is no particular restriction on the amount of curing agent used, but it is usually preferably 0.01 to 10 parts by mass relative to 100 parts by mass of the above-mentioned resin (preferably excluding the curing agent and the solvent). When using a curing agent such as a peroxide system (peroxide) or an azo polymerization initiator, the curing treatment is performed at an appropriate temperature and time in consideration of its half-life. The conditions in this case are arbitrary depending on the curing agent, but generally, a temperature range of about 50°C to 180°C is suitable.
[0058] The above-mentioned various resins, crosslinking materials and / or curing agents and their cured products used when the spherical silica powder and mixed powder of the present invention are used, in particular, for high-frequency substrate materials and insulating materials are described in the following patents, for example. Japanese Patent Publication No. 8-208856, Japanese Patent Publication No. 2017-75270, Japanese Patent Publication No. 2009-167268, Japanese Patent Publication No. 2011-68713, Japanese Patent Publication No. 2018-131519, Japanese Patent Publication No. 2016-534549, Japanese Patent Publication No. 2017-57352, WO2016-175325 International Publication Pamphlet, WO2016-175326 International Publication Pamphlet, WO2018-111337 International Publication Pamphlet.
[0059] The ratio of the spherical silica powder and the appropriately added mixed powder in the resin (resin composition) is appropriately selected according to the physical properties such as the dielectric constant and dielectric loss tangent as the target. For example, the amount of the resin used is appropriately selected in the range of 10 to 10,000 parts by mass relative to 100 parts by mass of the spherical silica powder. If the density of the resin is set to 1.2 g / cm 3 , the volume ratio of the resin is appropriately selected within the range of 1.8 to 94.3%.
[0060] By mixing the spherical silica powder of this embodiment into a resin, the dielectric loss tangent of the resin sheet after mixing the powder can be reduced. In addition, the resin sheet mixed with the spherical silica powder of this embodiment has good fluidity due to its low viscosity and excellent moldability.
[0061] Example
[0062] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to the Examples.
[0063] [Raw material silicon dioxide powder 1]
[0064] Spherical silica (made by Denka Co., Ltd.: FB-5D, specific surface area 2.3m 2 The results of the evaluation are shown in Table 1. The dielectric loss tangent of the resin sheet of the raw material silica powder 1 was 8.0×10 -4 , when using polypropylene (PP), it is 6.1×10 -4 .
[0065] [Raw material silicon dioxide powder 2]
[0066] Spherical silica (SFP-30M manufactured by Denka Co., Ltd., with a specific surface area of 6.0 m 2 / g) was subjected to heat treatment and evaluated in the same manner as in Example 1 described below. The evaluation results are shown in Table 1. The dielectric loss tangent of the resin sheet (PE) of the raw material silica powder 2 was 1.4×10 -3 .
[0067] [Raw material silicon dioxide powder 3]
[0068] Spherical silica (SFP-20M manufactured by Denka Co., Ltd., with a specific surface area of 11.5 m 2 / g) was subjected to heat treatment and evaluated in the same manner as in Example 1 described below. The evaluation results are shown in Table 1. The dielectric loss tangent of the resin sheet (PE) of the raw material silica powder 3 was 9.5×10 -3 .
[0069] [Raw material silicon dioxide powder 4]
[0070] Spherical silica (Denka Co., Ltd.: UFP-30, specific surface area 30.0m 2 / g) was subjected to heat treatment and evaluated in the same manner as in Example 1 described below. The evaluation results are shown in Table 1. The dielectric loss tangent of the resin sheet (PE) of the raw material silica powder 3 was 1.7×10 -3 .
[0071] [Example 1]
[0072] The raw material silica powder 1 (manufactured by Denka Co., Ltd.: FB-5D, specific surface area 2.3 m 2 / g) 50g of raw silicon dioxide is placed in a cylindrical container made of quartz glass, the cylindrical container is filled into a rotary kiln made of mullite, and heat-treated at a temperature of 900°C in the rotary kiln for 2 hours in a nitrogen atmosphere. After the heating treatment, the furnace is cooled to below 200°C and dried in a vacuum dryer (under an environment of 120°C - less than 133Pa) for 24 hours. It is stored in a vertical package (startup pack) of an aluminum package (PET / AL / PE laminated bag: manufactured by Nippon Sha Co., Ltd.) until various evaluations are performed. The evaluation results are shown in Table 2. It should be noted that the dielectric loss tangent of the resin sheet (PE) is 4.7×10 -4 .
[0073] [Examples 2 and 3]
[0074] The heat treatment and evaluation were performed in the same manner as in Example 1 except that the heat treatment temperature and time were set as shown in Table 2. Table 2 shows the evaluation results.
[0075] [Example 4]
[0076] 50 g of raw material silica powder 1 (manufactured by Denka Co., Ltd.: FB-5D, specific surface area 2.3 m 2 / g) as raw material silica was put into a cylindrical container made of quartz glass, the cylindrical container was filled into a rotary kiln made of mullite, and heat-treated at a temperature of 900°C in the rotary kiln for 2 hours in a nitrogen atmosphere. After the heat treatment, the furnace was cooled to below 200°C and dried in a vacuum dryer (under an environment of 120°C-less than 133Pa) for 24 hours. 1 part by mass of hexamethyldisilazane (Shin-Etsu Silicone, SZ-31; HMDS) was added as a surface treatment agent to 100 parts by mass of the recovered sample. The added powder was mixed with a vibrating mixer made by Resodyn, dried in a vacuum dryer (under an environment of 120°C-less than 133Pa) for 24 hours, and stored in an aluminum package as in Example 1 until various evaluations. The evaluation was carried out in the same manner as in Example 1. The evaluation results are shown in Table 2.
[0077] [Example 5]
[0078] The heat treatment and evaluation were performed in the same manner as in Example 4 except that vinyltrimethoxysilane (KBM-1003; vinyl, manufactured by Shin-Etsu Silicone Co., Ltd.) was used as the surface treatment agent.
[0079] [Example 6]
[0080] The raw material silicon dioxide was raw material silicon dioxide powder 2 (SFP-30M manufactured by Denka Co., Ltd., with a specific surface area of 6.0 m 2 The evaluation results are shown in Table 2.
[0081] [Example 7]
[0082] The evaluation results are shown in Table 2.
[0083] [Example 8]
[0084] The raw material silica powder 1 (manufactured by Denka Co., Ltd.: FB-5D, specific surface area 2.3 m 2 / g) 50g of raw silica was placed in an alumina crucible and heated at 1000°C for 4 hours in a nitrogen atmosphere in an electric furnace using Fuji Electric Industry's HIGHMULTI (carbon furnace). After the heating treatment, the furnace was cooled to below 200°C and dried in a vacuum dryer (120°C - less than 133Pa) for 24 hours. It was stored in a vertical package of an aluminum package (PET / AL / PE laminated bag: manufactured by Nipponsha Co., Ltd.) until various evaluations. The evaluation results are shown in Table 2.
[0085] [Example 9]
[0086] The raw material silicon dioxide was raw material silicon dioxide powder 2 (SFP-30M manufactured by Denka Co., Ltd., with a specific surface area of 6.0 m 2 / g), and the heating temperature and atmosphere were set as shown in Table 2. The heating treatment and evaluation were carried out in the same manner as in Example 8. The evaluation results are shown in Table 2.
[0087] [Example 10]
[0088] The heat treatment and evaluation were performed in the same manner as in Example 9 except that the heat treatment temperature, time, and atmosphere were set as shown in Table 2. Table 2 shows the evaluation results.
[0089] [Example 11]
[0090] The raw material silicon dioxide was raw material silicon dioxide powder 3 (SFP-20M manufactured by Denka Co., Ltd., with a specific surface area of 11.5 m 2 / g), and the heat treatment temperature and time were set as shown in the following Table 2, and the heat treatment and evaluation were performed in the same manner as in Example 1. The evaluation results are shown in Table 2.
[0091] [Example 12]
[0092] The raw material silicon dioxide was raw material silicon dioxide powder 4 (produced by Denka Co., Ltd.: UFP-30, specific surface area 30.0 m 2 / g), and the heat treatment temperature and time were set as shown in the following Table 2, and the heat treatment and evaluation were performed in the same manner as in Example 1. The evaluation results are shown in Table 2.
[0093] [Example 13]
[0094] The heat treatment and evaluation were performed in the same manner as in Example 1 except that the heat treatment temperature and time were set as shown in Table 2. Table 2 shows the evaluation results.
[0095] [Comparative Examples 1 to 4]
[0096] The heat treatment and evaluation were performed in the same manner as in Example 1 except that the heat treatment temperature, time, raw silica powder, and atmosphere were set as shown in Table 3. Table 3 shows the evaluation results.
[0097] The properties of each sample were evaluated by the following method. The evaluation results are shown in Tables 1 to 3.
[0098] [Average roundness]
[0099] After fixing the powder on the sample stand with a carbon tape, osmium coating was performed, and an image with a magnification of 500 to 50,000 times and a resolution of 1280×1024 pixels taken with a scanning electron microscope (manufactured by JEOL Ltd., JSM-7001F SHL) was read into a personal computer. The image was analyzed using an image analyzer (manufactured by Nippon Roper, Image-Pro Premier Ver.9.3), and the projected area (S) of the particle (powder particle) and the projected circumference length (L) of the particle were calculated, and the roundness was calculated by the following formula (1). The roundness was calculated for any 200 particles of 1 to 10 μm when the raw silica was FB-5D, and for any 200 particles of 0.2 to 1 μm when the raw silica was SFP-30M, and the average value was taken as the average roundness.
[0100] Roundness = 4πS / L 2 ……Formula (1)
[0101] [density]
[0102] 1.2 g of the powder was placed in a sample cell for measurement, and the density was measured by a gas (helium) replacement method using a dry density meter ("AccuPyc II1340" manufactured by Shimadzu Corporation).
[0103] [Specific surface area]
[0104] 1 g of sample was filled in the measuring cell, and the specific surface area was measured using Macsorb HM model-1201 fully automatic specific surface area measuring device (BET one-point method) manufactured by Mountech. The degassing conditions before the measurement were 200°C-10 minutes. The adsorption gas was nitrogen.
[0105] [B / A]
[0106] The integrated intensity ratio of B (hydrogen-bonding silanol group) to A (isolated silanol group) was measured by diffuse reflection method in air atmosphere using a Fourier transform infrared spectrophotometer (Frontier infrared spectrometer manufactured by PerkinElmer) (resolution 8.0 cm -1 , cumulative number of times 32 times), from the diffuse reflectance spectrum obtained, in the range of 3800-2875cm-1 Draw a baseline between them and calculate 3735cm -1 ~3755cm -1 The peak intensity of isolated silanol group, 3660cm -1 ~3680cm -1 The peak intensity ratio of the hydrogen-bonding silanol group was calculated.
[0107] [Dehydrated water content]
[0108] Using a temperature rise degassing analyzer (EMD-WA1000S / W manufactured by Electronic Science Co., Ltd.; TDS), the temperature of the upper thermocouple was raised from 25°C to 1000°C at 30°C / min in an atmospheric atmosphere, and the number of H2O desorbed molecules was calculated from the area value of the mass spectrum (m / z=18) in the range of 500°C to 1000°C. The carbon sheet, sample powder (10 mg), and carbon sheet were placed in sequence on a quartz sample dish, and the measurement was performed in this state.
[0109] [Evaluation of Dielectric Properties]
[0110] Spherical silica powder and polyethylene (PE) powder (FLO-THENE UF-20S manufactured by Sumitomo Seika Chemicals Co., Ltd.) or polypropylene (PP) powder (FLO-BLEN QB200 manufactured by Sumitomo Seika Chemicals Co., Ltd.) were weighed so that the filling amount of the spherical silica powder after heat treatment was 40 volume %, and mixed using a vibration mixer manufactured by Resodyn (acceleration 60 g, processing time 2 minutes). The obtained mixed powder was weighed to a predetermined volume (so that the thickness was 0.3 mm), placed in a metal frame with a diameter of 3 cm, and formed into sheets using a hot press ("IMC-1674-A Model" manufactured by Imoto Seisakusho Co., Ltd.) at 140°C and 10 MPa for 15 minutes in the case of PE, and at 190°C and 10 MPa for 60 minutes in the case of PP, to prepare evaluation samples. The thickness of the evaluation sample sheet was 0.3 mm, and the shape and size did not affect the evaluation results as long as it could be mounted on the measuring instrument, and was 1.5 cm square.
[0111] The dielectric properties were measured by connecting a 36GHz cavity resonator (Samtec) to a vector network analyzer (85107, Keysight Technologies), installing a sample (1.5cm square, 0.3mm thick) in a manner that blocked a hole with a diameter of 10mm set in the resonator, and measuring the resonant frequency (f0) and the unloaded Q value (Qu). The sample was rotated for each measurement, and the measurement was repeated 5 times in the same manner, and the average values of the obtained f0 and Qu were taken as the measured values. The dielectric constant was calculated from f0 using analytical software (Samtec software), and the dielectric loss tangent was calculated from Qu. The measurement temperature was 20°C and the humidity was 60% RH.
[0112] In addition, the dielectric loss tangent of the resin sheet measured by mixing the raw material spherical silica powders 1 to 4 with resin is set to a, and the dielectric loss tangent of the resin sheet measured by mixing the spherical silica powders of the examples and comparative examples with resin is set to b, and the reduction rate (%) of the dielectric loss tangent of the resin sheet itself is calculated by formula (2).
[0113] The reduction rate of the dielectric loss tangent of the resin sheet itself (%) = {1-(b / a)}×100... Formula (2)
[0114] [Table 1]
[0115] Table 1
[0116]
[0117]
[0118] [Table 3]
[0119] Table 3
[0120] unit Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Types of raw silica powder - FB-5D FB-5D SFP-30M FB-5D Heating temperature ℃ 500 850 400 800 Heating time h 2 0.5 2 1 atmosphere - Nitrogen Nitrogen Nitrogen atmosphere Average roundness - 0.95 0.95 0.95 0.96 density <![CDATA[g / cm 3 ]]> 2.2 2.2 2.2 2.2 Specific surface area <![CDATA[m 2 / g]]> 2.4 2.4 6.0 2.4 B / A - 4.6 3.3 3.1 3.0 Molecular weight of water mmol / g 0.015 0.011 0.021 0.011 Resin Type - PE PE PE PE Dielectric constant of resin sheet - 2.8 2.8 2.8 2.8 Dielectric loss tangent of resin sheet - 6.8E-04 7.2E-04 1.2E-03 6.9E-04 Dielectric loss tangent reduction rate % 15 10 14 14
[0121] As a result, the resin sheets containing the spherical silica powders of Examples 1 to 13 had dielectric loss tangents suppressed to be lower than those of the resin sheets containing the spherical silica powders of Comparative Examples 1 to 4.
[0122] [Example 14]
[0123] As conjugated diene polymers, 1,2-polybutadiene (liquid polybutadiene manufactured by Nippon Soda Co., Ltd.: product name B-1000) and bifunctional polyphenylene ether oligomer (OPE-2St manufactured by Mitsubishi Gas Chemical Co., Ltd., number average molecular weight 1200) were used. OPE-2St uses a polyphenylene ether oligomer obtained as follows: a toluene solution product manufactured by Mitsubishi Gas Chemical Co., Ltd. is further diluted with toluene, a large amount of methanol is further added to precipitate methanol, air-dried, and then dried under reduced pressure to obtain a powdered polyphenylene ether oligomer. PERCUMYL D manufactured by NOF Corporation is used as a peroxide. 1,2-polybutadiene, OPE-2St, and peroxide are dissolved in toluene in the formulation of Table 4 (unless otherwise specified, the unit is mass parts) to prepare a varnish. Relative to 70% by volume of the resin component (total of 1,2-polybutadiene and OPE-2St) in the varnish, add 30% by volume of the powder obtained in Example 10 (SFP-30M treated product), stir and mix evenly, and inject into a polytetrafluoroethylene mold, while decompressing and slowly heating to 60°C, keep it for a day and night, and remove the solvent. The obtained uncured sheet is pressurized at 2MPa and heated at 6°C / min using a vacuum heating press, and kept at 220°C for 1 hour, thereby obtaining a cross-linked (cured) sheet with a thickness of 0.5mm. The evaluation of dielectric properties is carried out in the same manner as in Example 1. As shown in Table 4, the dielectric loss tangent value of the sheet obtained in this embodiment is a significantly lower value than that of Comparative Example 5 described later.
[0124] [Comparative Example 5]
[0125] A resin sheet was prepared in the same manner as in Example 14 except that the powder (SFP-30M treated product) obtained in Example 10 was replaced with an SFP-30M untreated product, and the dielectric properties were evaluated in the same manner as in Example 1. Table 4 shows the results.
[0126] [Table 4]
[0127] Table 4
[0128]
[0129] Industrial Applicability
[0130] The spherical silica powder of the present invention can be used as a filler capable of lowering the dielectric loss tangent of a base material compared with conventional spherical silica when filled in a resin material.
Claims
1. A spherical silicon dioxide powder, characterized in that: When the temperature is raised from 25°C to 1000°C at 30°C / min, the number of water molecules released at 500°C to 1000°C is less than 0.008 mmol / g, and the specific surface area is 2.2 to 6.2 m 2 / g; The wave number of the silica powder measured by diffuse reflectance FT-IR method is 3735 cm -1 ~3755cm -1 The peak intensity is set to A and the wave number is 3660 cm -1 ~3680cm -1 When the peak intensity of is set to B, B / A is less than 3.0; The average roundness of the spherical silica powder is 0.85 or more.
2. The spherical silicon dioxide powder according to claim 1, characterized in that The surface has been treated with a surface treatment agent.
3. The spherical silicon dioxide powder according to claim 1 or 2, characterized in that Used in combination with resin. 4 . A resin composition comprising the spherical silica powder according to claim 1 and a resin.
5. The resin composition according to claim 4, wherein The resin is at least one selected from hydrocarbon elastomers, polyphenylene ethers, aromatic polyene resins and bismaleimide resins.
6. A cured product obtained by curing the resin composition according to claim 4 or 5.
Citation Information
Patent Citations
Method for producing resin varnish containing semi-IPN composite thermosetting resin, as well as resin varnish for printed wiring board, prepreg, and metal-clad laminate using the same
JP2008291227A
Low thermal expansion low dielectric loss prepreg and its applied article
JP2009167268A
Coverlay film
JP2011068713A
Resin composition for dielectric and high-frequency dielectric device
JP2014024916A
Circuit material, circuit laminate, and method for manufacturing the same
JP2016534549A
